2022
DOI: 10.1128/aac.00021-22
|View full text |Cite
|
Sign up to set email alerts
|

Search for a Shared Genetic or Biochemical Basis for Biofilm Tolerance to Antibiotics across Bacterial Species

Abstract: Is there a universal genetically programmed defense providing tolerance to antibiotics when bacteria grow as biofilms? A comparison between biofilms of three different bacterial species by transcriptomic and metabolomic approaches uncovered no evidence of one. Single-species biofilms of three bacterial species ( Pseudomonas aeruginosa , Staphylococcus aureus , and Acinetobacter baumannii ) were grown in vitro for 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 113 publications
1
1
0
Order By: Relevance
“…This suggests that the fundamental mechanisms behind reduced biofilm susceptibility could be similar for different classes of antibiotics and in different organisms, even when it is not possible to identify mutations, mutated genes, or differences in metabolism or gene expression shared between different organisms. As such, data from experimental evolution are in line with the conclusion of a recent study that could not find evidence for a common genetic or biochemical basis for antimicrobial tolerance in biofilms but concluded that many genes, proteins, and metabolic pathways collectively determine the physiological state and susceptibility of bacterial cells in a biofilm 132 .…”
Section: Looking At Biofilm Antimicrobial Susceptibility Through the ...supporting
confidence: 69%
“…This suggests that the fundamental mechanisms behind reduced biofilm susceptibility could be similar for different classes of antibiotics and in different organisms, even when it is not possible to identify mutations, mutated genes, or differences in metabolism or gene expression shared between different organisms. As such, data from experimental evolution are in line with the conclusion of a recent study that could not find evidence for a common genetic or biochemical basis for antimicrobial tolerance in biofilms but concluded that many genes, proteins, and metabolic pathways collectively determine the physiological state and susceptibility of bacterial cells in a biofilm 132 .…”
Section: Looking At Biofilm Antimicrobial Susceptibility Through the ...supporting
confidence: 69%
“…One of the hallmarks of chronic P. aeruginosa infections is that they occur in biofilms, where the bacterial cells and their extracellular matrices are bound to a surface, such as host tissue or artificial implant devices [ 14 , 15 ]. As a result, much research has been devoted to characterizing the physiological differences of P. aeruginosa growing in biofilms compared to cells growing in planktonic culture, with an emphasis on identifying factors that make P. aeruginosa biofilms difficult to clear by antibiotics (e.g., [ 16 , 17 , 18 ]). An important factor for bacterial biofilm growth is that the cells are physiologically heterogeneous [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%